2020
DOI: 10.3390/jcm9103268
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Tumor Location in T2 Gallbladder Cancer: A Korea Tumor Registry System Biliary Pancreas (KOTUS-BP) Database Analysis

Abstract: Background: T2 gallbladder cancer (GBC) is subdivided into T2a and T2b by the American Joint Committee on Cancer (AJCC) 8th edition. However; there is a lack of evidence for the prognostic significance of tumor location and validation with large-scale studies is needed. The aims of this study were to investigate the clinical features and clinical outcomes of T2 GBC according to tumor location and determine the prognostic significance of tumor location and an appropriate surgical strategy. Methods: Between 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…Numerous studies have confirmed that ACT can significantly improve overall survival outcomes in patients with biliary tract malignancies with lymph node metastasis and positive surgical margins, consistent with our results. [32,33] However, ACT did not significantly improve the prognosis of patients who achieved a TO in this study.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Numerous studies have confirmed that ACT can significantly improve overall survival outcomes in patients with biliary tract malignancies with lymph node metastasis and positive surgical margins, consistent with our results. [32,33] However, ACT did not significantly improve the prognosis of patients who achieved a TO in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…Numerous studies have confirmed that ACT can significantly improve overall survival outcomes in patients with biliary tract malignancies with lymph node metastasis and positive surgical margins, consistent with our results. [32,33] However, ACT did not significantly improve the prognosis of patients who achieved a TO in this study. Ostwal et al [34] found that gemcitabine combined with cisplatin could improve the prognosis of stage IIIII GBC after radical resection without serious side effects, and patients tolerated this regimen well.…”
Section: Discussionmentioning
confidence: 56%
“…In spite of its limited depth of invasion into the gallbladder wall, T2 GBC generally has a high rate of LN metastasis of up to 50% [ 9 , 19 , 20 , 21 ]. All the studies included in the present meta-analysis showed that LN metastasis was a significant prognostic factor in multivariate analysis, and they also demonstrated that a T2b tumor has a higher possibility of LN metastasis than a T2a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The gallbladder has a unique anatomy, and this anatomy might be associated with the tumor invasion, the mode of tumor spread and finally prognosis. The hepatic side of the gallbladder is attached directly to the liver only by loose connective tissue without serosa, and it has dense arterial, venous and lymphatic communications to allow easy invasion to the liver [ 9 ]. In contrast, the peritoneal side of the gallbladder is free from the adjacent organs.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor stage of GBC was determined according to the American Cancer TNM Staging System Joint Committee (8th Edition) classification system. 8,9 T refers to the primary tumor stage, which is divided into Tis, T1a, T1b, T2a, T2b, T3, and T4 on account of the depth of tumor invasion. N refers to regional lymph node metastasis, which is divided into N0, N1, and N2.…”
Section: Laboratory Testing and Clinical Datamentioning
confidence: 99%